2017
DOI: 10.1007/s00787-017-0983-1
|View full text |Cite
|
Sign up to set email alerts
|

An international qualitative study of ability and disability in ADHD using the WHO-ICF framework

Abstract: This is the third in a series of four cross-cultural empirical studies designed to develop International Classification of Functioning, Disability and Health (ICF, and Children and Youth version, ICF(-CY) Core Sets for Attention-Deficit Hyperactivity Disorder (ADHD). To explore the perspectives of individuals diagnosed with ADHD, self-advocates, immediate family members and professional caregivers on relevant areas of impairment and functional abilities typical for ADHD across the lifespan as operationalized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 32 publications
9
40
0
3
Order By: Relevance
“…This standardized system can serve to facilitate multidisciplinary assessments by enabling more efficient communication between different professionals and organizations. Corroborating our own research [15,16,41], this study identified relevant environmental factors across different chapters of the ICF-CY, highlighting the importance of taking into account all types of facilitators and barriers in the environment when conducting functional assessments related to ADHD. One of the most referenced chapters in the environmental factors component was attitudes, which might be explained by the fact that ADHD is still not fully accepted as a bona-fide medical condition among some community members [53,54].…”
Section: Identified Icf-cy Categoriesmentioning
confidence: 67%
See 4 more Smart Citations
“…This standardized system can serve to facilitate multidisciplinary assessments by enabling more efficient communication between different professionals and organizations. Corroborating our own research [15,16,41], this study identified relevant environmental factors across different chapters of the ICF-CY, highlighting the importance of taking into account all types of facilitators and barriers in the environment when conducting functional assessments related to ADHD. One of the most referenced chapters in the environmental factors component was attitudes, which might be explained by the fact that ADHD is still not fully accepted as a bona-fide medical condition among some community members [53,54].…”
Section: Identified Icf-cy Categoriesmentioning
confidence: 67%
“…Others emphasized the role that ADHD played in taking initiative to create new hobbies or participate in social events. Contrary to the expert survey and qualitative study [15,16], this study identified new aspects of strengths in ADHD, such as making friends and having good relationships with family members. Some participants mentioned that they were able to form meaningful social relationships with their loved ones after many years of practice and learning, while others felt that ADHD made it automatically easier for them to approach people and initiate meaningful interactions that later led to deeper social bonds.…”
Section: Adhd-related Strengthsmentioning
confidence: 80%
See 3 more Smart Citations